Woman in eyes of medieval culture: antifeminism as fobia - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to one of the most serious consequences of axiological ostracism, which has been subjected to the phenomenon of earthly love in Medieval European culture – namely, the formation of antifeminism. It is shown that this phenomenon extends far beyond the ordinary household invectives against women, because it had formed not only the deep cultural setting of the medieval worldview, but real phobia. This article discusses two directions of it’s realization: the negative perception of female sexuality as dangerous, on the one hand, and sustainable binding in the mass consciousness of the phenomenon of women with magic and sorcery – on the other.